Transfer of the Symbiotic Plasmid of Rhizobium etli CFN42 to Endophytic Bacteria Inside Nodules - Bañuelos-Vazquez, Luis Alfredo; Cazares, Daniel; Rodríguez, Susana; Cervantes-De la Luz, Laura; Sánchez-López, Rosana; Castellani, Lucas G.; Tejerizo, Gonzalo Torres; Brom, Susana (Frontiers in Microbiology, 2020)
Conjugative transfer is one of the mechanisms allowing diversification and evolution of bacteria. Rhizobium etli CFN42 is a bacterial strain whose habitat is the rhizosphere and is able to form nodules as a result of the nitrogen-fixing symbiotic relationship it may establish with the roots of Phaseolus vulgaris. R. etli CFN42 contains one chromosome and six large plasmids (pRet42a - pRet42f). Most of the genetic information involved in the establishment of the symbiosis is localized on plasmid pRet42d, named as the symbiotic plasmid (pSym). This plasmid is able to perform conjugation, using pSym encoded transfer genes controlled by the RctA/RctB system. Another plasmid of CFN42, pRet42a, has been shown to perform conjugative transfer not only in vitro, but also on the surface of roots and inside nodules, using other rhizobia as recipients. In addition to the rhizobia involved in the formation of nodules, these structures have been shown to contain endogenous bacteria from different genera and species. In this work, we have explored the conjugative transfer of the pSym (pRet42d) from R. etli CFN42 to endogenous bacteria as putative recipients, using as donor a CFN42 derivative labeled with GFP in the pRet42d and RFP in the chromosome. We were able to isolate some transconjugants, which inherit the GFP, but not the RFP marker. Some of them were identified, analyzed and evaluated for their ability to nodulate. We found transconjugants from genera such as Stenotrophomonas, Achromobacter, and Bacillus, among others. Although all the transconjugants carried the GFP marker, and nod, fix and nif genes from pRet42d, not all were able to nodulate. Ultrastructure microscopy analysis showed some differences in the structure of the nodules of one of the transconjugants. A replicon of the size of pRet42d (371 Kb) could not be visualized in the transconjugants, suggesting that the pSym or a segment of the plasmid is integrated in the chromosome of the recipients. These findings strengthen the proposal that nodules constitute a propitious environment for exchange of genetic information among bacteria, in addition to their function as structures where nitrogen fixation and assimilation takes place.